2022
DOI: 10.1007/s00167-022-07296-6
|View full text |Cite
|
Sign up to set email alerts
|

Fear of reinjury following primary anterior cruciate ligament reconstruction: a systematic review

Abstract: Purpose This review aims to elucidate the most commonly reported method to quantify fear of reinjury or kinesiophobia and to identify key variables that inluence the degree of kinesiophobia following primary anterior cruciate ligament reconstruction (ACLR). Methods A systematic search across three databases (Pubmed, Ovid (MEDLINE), and EMBASE) was conducted from database inception to August 7th, 2022. The authors adhered to the PRISMA guidelines and the Cochrane Handbook for Systematic Reviews of Interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…The findings of this study with regard to kinesiophobia and pain are consistent with the literature. In previous studies, kinesiophobia and TSK measures have been shown to be mild‐moderately correlated with pain in patients with shoulder and knee pathology ( r = 0.16–0.43) [3, 24, 37]. Additionally, greater kinesiophobia has been shown to lead to lower quality of life and greater disability in patients with chronic musculoskeletal pain [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study with regard to kinesiophobia and pain are consistent with the literature. In previous studies, kinesiophobia and TSK measures have been shown to be mild‐moderately correlated with pain in patients with shoulder and knee pathology ( r = 0.16–0.43) [3, 24, 37]. Additionally, greater kinesiophobia has been shown to lead to lower quality of life and greater disability in patients with chronic musculoskeletal pain [18].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, data were inconsistently reported, with many authors reporting only pooled data, and not responding to requests for primary data tables limiting the ability to perform pooled data analysis. Another limitation was that TSK‐17 and TSK‐11 were both used to assess kinesiophobia, despite both scales being valid and reliable [24]. A major strength of this systematic review is that it includes all relevant literature regarding the effect that kinesiophobia has on physical function performance measures and PROMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggests psychosocial factors such as kinesiophobia (fear of movement/reinjury), preoperative mental health and pain catastrophizing may influence return to sport [9,10]. While kinesiophobia has been predominantly recognized as affecting outcomes following anterior cruciate ligament reconstruction (ACLR) [11][12][13], shoulder arthroscopy [14][15][16], hip [17] and total knee arthroplasty (TKA) [18,19], there is still limited evidence describing it's effects on RTS and clinical outcomes after OCA transplantation of the knee [20].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst these options improve pain and range of motion, instability in the joint tends to appear years after the surgery, with an increased risk of rupture in patients who underwent partial resection [26]. Additionally, it is well known that there are increased psychological symptoms associated with delayed treatment of ACL injuries [21]; therefore, it is important to understand what factors predispose an individual to develop mucoid degeneration of the ACL so that those who are in need of treatment are monitored for early operative management if necessary.…”
Section: Introductionmentioning
confidence: 99%